Assessment methods for impact of environmentally friendly entrepreneurship and driving forces to the quality of environment - Frolova, L.; Kauzena, D. (Mathematical Modelling and Analysis, 2002)
Environmentally friendly entrepreneurship (further – EFE) is one of the tools for improvement environmental quality. There might be made theoretical approaches, how quantitatively large is the impact of the EFE in changes of the quality of environment. In this field theoretical suggestion is prior to practice, because in the most of countries there is domination of several cases, but it could not be used as overall tendency [8; 10]. Opposite impact to quality of environment might be created by driving forces (driving forces are economical indicators, which stimulate changes in quality of environment) [1] like overcon‐sumption, growth of gross domestic product (further – GDP) etc. The article will highlight three possible approaches: 1) the assessment of EFE and driving forces to environmental quality; 2) quantitative analysis of interaction between environmental pressure (pressure indicators characterized impact of enterprises made to environment) indicators and driving forces indicators. In the second part there will be compared four countries: Baltic states and Sweden and 3) descriptive analysis of interaction between enterprise size and positive arrangements according environmental protection in Latvia in 1999 and 2001. Mainly there will be used the method of mathematical modelling [6] – descriptive, regression and power models and their attributes.Aplinkai draugiško verslumo ir varančiųjų jėgų įtakos aplinkos kokybei metodų įvertinimasSantrauka. Aplinkai draugiškas verslumas (ADV) ‐ viena iš priemonių aplinkos kokybės gerinimui. Galima bandyti teoriškai parodyti, kaip aplinkos kokybės pasikeitimus įtakoja ADV. Šioje srityje teoriniai pasiūlymai nei praktinis panaudojimas, kadangi daugumoje šalių vyrauja skirtingi būdai, bet tai negali būti naudojama kaip bendroji tendencija. Aplinkos kokybei priešingą įtaką gali kurti varančios jėgos (varančios jėgos yra ekonominiai indikatoriai, kurie stimuliuoja aplinkos kokybės pasikeitimus) tokios kaip pervartojimas, bendrojo vidaus produkto augimas ir t.t. Straipsnyje nušviečiami trys galimi aspektai: 1) ADV ir varančiųjų jėgų įtakos aplinkos kokybei įvertinimas; 2) kiekybinė sąveikos tarp aplinkos spaudimo indikatorių (šie indikatoriai charakterizuoja įmonių spaudimą aplinkai) ir varančiųjų jėgų indikatorių. Antrojoje dalyje lyginamos keturios šalys: Baltijos šalys ir Švedija ir 3) sąveikos tarp įmonės dydžio ir teigiamu aplinkos apsaugos priemonių Latvijoje 1999 ir 2001 m. analizė. Čia naudojamas matematinis modeliavimas ‐ aprašomieji, regresiniai ir jėgos modeliai ir jų atributai. First Published Online: 14 Oct 2010